Honeybee Iflaviruses Pack Specific tRNA Fragments from Host Cells in Their Virions - Šimonová, Anna; Romanská, Veronika; Benoni, Barbora; Škubník, Karel; Šmerdová, Lenka; Procházková, Michaela; Spustová, Kristina; Moravčík, Ondřej; Gahurova, Lenka; Pačes, Jan; Plevka, Pavel; Cahová, Hana (Chembiochem, 2022)
The Picornavirales include viruses that infect vertebrates, insects, and plants. It was believed that they pack only their genomic mRNA in the particles; thus, we envisaged these viruses as excellent model systems for studies of mRNA modifications. We used LC-MS to analyze digested RNA isolated from particles of the sacbrood and deformed wing iflaviruses as well as of the echovirus 18 and rhinovirus 2 picornaviruses. Whereas in the picornavirus RNAs we detected only N6 -methyladenosine and 2'-O-methylated nucleosides, the iflavirus RNAs contained a wide range of methylated nucleosides, such as 1-methyladenosine (m1 A) and 5-methylcytidine (m5 C). Mapping of m1 A and m5 C through RNA sequencing of the SBV and DWV RNAs revealed the presence of tRNA molecules. Both modifications were detected only in tRNA. Further analysis revealed that tRNAs are present in form of 3' and 5' fragments and they are packed selectively. Moreover, these tRNAs are typically packed by other viruses.
Keywords: LC-MS; messenger RNA; RNA transferová; virion; Picornavirales; RNA, Transfer; human rhinovirus type 2; RNA; RNA methylation; Nucleosides; RNA, Messenger; zvířata; nukleosidy; tRNA fragments; včely; human Echovirus 18; Bees; Virion; Animals